Mesenchymal Stem Cells and Induced Bone Marrow‐Derived Macrophages Synergistically Improve Liver Fibrosis in Mice. (5th November 2018) - Watanabe, Yusuke; Tsuchiya, Atsunori; Seino, Satoshi; Kawata, Yuzo; Kojima, Yuichi; Ikarashi, Shunzo; Starkey Lewis, Philip J.; Lu, Wei‐Yu; Kikuta, Junichi; Kawai, Hirokazu; Yamagiwa, Satoshi; Forbes, Stuart J.; et al.
Abstract: We describe a novel therapeutic approach for cirrhosis using mesenchymal stem cells (MSCs) and colony‐stimulating factor‐1‐induced bone marrow‐derived macrophages (id‐BMMs) and analyze the mechanisms underlying fibrosis improvement and regeneration. Mouse MSCs and id‐BMMs were cultured from mouse bone marrow and their interactions analyzed in vitro. MSCs, id‐BMMs, and a combination therapy using MSCs and id‐BMMs were administered to mice with CCl4 ‐induced cirrhosis. Fibrosis regression, liver regeneration, and liver‐migrating host cells were evaluated. Administered cell behavior was also tracked by intravital imaging. In coculture, MSCs induced switching of id‐BMMs toward the M2 phenotype with high phagocytic activity. In vivo, the combination therapy reduced liver fibrosis (associated with increased matrix metalloproteinases expression), increased hepatocyte proliferation (associated with increased hepatocyte growth factor, vascular endothelial growth factor, and oncostatin M in the liver), and reduced blood levels of liver enzymes, more effectively than MSCs or id‐BMMs monotherapy. Intravital imaging showed that after combination cell administration, a large number of id‐BMMs, which phagocytosed hepatocyte debris and were retained in the liver for more than 7 days, along with a few MSCs, the majority of which were trapped in the lung, migrated to the fibrotic area in the liver. Host macrophages and neutrophils infiltrated after combination therapy and contributed to liver fibrosis regression and promoted regeneration along with administered cells. Indirect effector MSCs and direct effector id‐BMMs synergistically improved cirrhosis along with host cells in mice. These studies pave the way for new treatments for cirrhosis.Stem Cells Translational Medicine 2019;8:271&284 Abstract : Combination therapy using mesenchymal stem cells (MSCs) and induced bone marrow‐derived macrophages (id‐BMMs), synergistically regressed liver fibrosis and promoted liver regeneration with recruiting host macrophages and neutrophils. Indirect effector MSCs changed the polarity of direct effector id‐BMMs toward M2 phenotype with high antifibrosis, proregeneration, and phagocytosis effect. Intravital imaging revealed the behavior of MSCs and id‐BMMs and mechanisms of this therapy.